Visualisasi Ciri Khas Daerah Rejang Lebong dengan Mengaplikasikan Huruf Kaganga dalam Karya Seni Batik Lukis - Adila, Triana; Pebriyeni, Eliya (EduInovasi: Journal of Basic Educational Studies, 2025)
This final project aims to visualize the distinctive characteristics of Rejang Lebong through the application of the Kaganga script in batik painting artworks. The creation of this work is motivated by the intention to preserve the Kaganga script, which has become less known to the public, and to introduce the cultural and natural richness of Rejang Lebong to younger generations. The creative process consists of five stages: preparation, elaboration, synthesis, realization, and completion. The artworks were created using primissima mori fabric measuring 50×45 cm, employing the batik painting technique with Remazol dyes through the colet method, and color fixation using waterglass to strengthen and preserve color durability. The final result consists of ten batik paintings depicting distinctive objects of Rejang Lebong such as the Rafflesia flower, Kibut flower, Danau Mas, traditional Rejang house, keris, Bukit Kaba, lemea, cerano, and traditional clothing, with the Kaganga script applied as supporting motifs and isen-isen to enhance the aesthetic value. These artworks implement visual elements and design principles such as line, form, color, texture, unity, balance, proportion, rhythm, and contrast, resulting in harmonious and visually appealing compositions. Through this work, it is expected that society will gain a deeper appreciation and awareness of Rejang Lebong’s local culture and the importance of preserving regional cultural heritage.